Effect of having private health insurance on the use of health care services: the case of Spain - David Cantarero-Prieto; Marta Pascual-Sáez; Noelia Gonzalez-Prieto (BMC, 2017)
Abstract Background Several stakeholders have undertaken initiatives to propose solutions towards a more sustainable health system and Spain, as an example of a European country affected by austerity measures, is looking for ways to cut healthcare budgets. Methods The aim of this paper is to study the effect of private health insurance on health care utilization using the latest micro-data from the European Community Household Panel (ECHP), the Spanish National Health Survey (SNHS) and the European Union Statistics on Income and Living Conditions (EU-SILC). We use matching techniques based on propensity score methods: single match, four matches, bias-adjustment and allowing for heteroskedasticity. Results The results demonstrate that people with a private health insurance, use the public health system less than individuals without double health insurance coverage. Conclusions Our conclusions are useful when policy makers design public-private partnership policies.